The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.bbrc.2015.08.089
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of DNA methylation changes in two rice genotypes under salt stress and subsequent recovery

Abstract: DNA methylation, which is one of the best understood epigenetic phenomena, plays an important role in plant responses to environmental stimuli. The rice introgression line IL177-103 and its recurrent parent IR64, which show contrasting salt stress tolerance, were used to characterize DNA methylation changes under salt stress and subsequent recovery using methylation-sensitive amplified polymorphism (MSAP) analysis. The introgression line IL177-103 showed significantly improved tolerance to salinity, as represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 35 publications
(45 reference statements)
6
43
0
Order By: Relevance
“…Certainly, it has been widely reported that salinity imposes extensive, genome-wide modification of DNA methylation patterns, with more methylation changes being reported in leaves when compared with roots [25][26][27]33,[57][58][59][60], a trend that is clearly in accordance with our findings. Taken at face value, the greater abundance of salt-induced methylation changes in leaves than in roots appears counterintuitive, since roots are in direct contact with salt stress.…”
Section: Salt Induces Different Changes To the Dna Methylation Of Leasupporting
confidence: 83%
“…Certainly, it has been widely reported that salinity imposes extensive, genome-wide modification of DNA methylation patterns, with more methylation changes being reported in leaves when compared with roots [25][26][27]33,[57][58][59][60], a trend that is clearly in accordance with our findings. Taken at face value, the greater abundance of salt-induced methylation changes in leaves than in roots appears counterintuitive, since roots are in direct contact with salt stress.…”
Section: Salt Induces Different Changes To the Dna Methylation Of Leasupporting
confidence: 83%
“…This result is in agreement with the widely accepted view that closely related species may possess some methylome flexibility, and consequently gene expression diversity (Postnikova et al, 2013). For example, rice cultivars with different salinity-tolerance capacities exhibit different DNA methylation patterns in response to salinity stress (Ferreira et al, 2015;Garg et al, 2015;Wang et al, 2015b). Overall, the mean number of methylated MSAP loci increased while the number of hemi and non-methylated loci decreased (Figure 4).…”
Section: Discussionsupporting
confidence: 89%
“…This variation can be detected by developing suitable molecular genetic and epigenetic markers associated with salinity tolerance (Wang et al, 2015b). The construction of genetic maps using DNA markers and the localization of quantitative trait loci are routine practices in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide DNA methylation under various abiotic and biotic stresses have been recorded for various plant species (Kou et al, 2011; Wang et al, 2011, 2015; Karan et al, 2012; Colaneri and Jones, 2013; Fan et al, 2013; Shan et al, 2013; Gao et al, 2014). Researchers also aspired to disclose the associations between DNA methylation and stress-tolerance via artificial generation of DNA methylation differences between two genotypes of contrasting tolerances (Wang et al, 2011; Gayacharan and Joel, 2013; Gao et al, 2014; Ferreira et al, 2015; Garg et al, 2015; Wang W. et al, 2016).…”
Section: Introductionmentioning
confidence: 99%